2022
DOI: 10.1007/s11055-022-01229-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychoemotional Disorders and Sleep Impairments in Patients with COVID-19

Abstract: Objectives. To study the prevalence of anxious-depressive disorders and sleep impairments in their structure among patients hospitalized with the new coronavirus infections (COVID-19) and to develop differential guidelines for their treatment in COVID-19 patients. Materials and methods. This report presents preliminary results from our own observations. We report here analysis of data from 119 patients (age 47-69 years, male and female) obtained at detailed interviews, including using telemedicine technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Twelve studies 17,22,24,26,29,33,34,36,42,44,45,47 used 12 different mental health-related measures: the Patient Health Questionnaire-9 (PHQ-9; N = 3), the Hospital and Anxiety Depression Scale (HADS; N = 2), Generalised Anxiety Disorder-7 (GAD-7; N = 2), the Beck Anxiety Inventory (BAI; N = 1), the Beck Depression Inventory (BDI; N = 1), the Child Depression Inventory (CDI, N = 1), the Child Post-Traumatic Stress Reaction Index (CPTS-RI; N = 1), the Harvard Trauma Questionnaire (HTQ; N = 1), the Perceived Stress Scale (PSS-10; N = 1), the Screen for Child Anxiety Related Disorders (SCARED; N = 1), the Self-Rating Anxiety Scale (SAS; N = 1) and the Self-Rating Depression Scale (SDS; N = 1). Twelve studies used one or more sleep-related QOL measures, 13,17,23,26,29,[33][34][35][36]42,44,47 with the most popular being the Pittsburgh Sleep Quality Index (PSQI; N = 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies 17,22,24,26,29,33,34,36,42,44,45,47 used 12 different mental health-related measures: the Patient Health Questionnaire-9 (PHQ-9; N = 3), the Hospital and Anxiety Depression Scale (HADS; N = 2), Generalised Anxiety Disorder-7 (GAD-7; N = 2), the Beck Anxiety Inventory (BAI; N = 1), the Beck Depression Inventory (BDI; N = 1), the Child Depression Inventory (CDI, N = 1), the Child Post-Traumatic Stress Reaction Index (CPTS-RI; N = 1), the Harvard Trauma Questionnaire (HTQ; N = 1), the Perceived Stress Scale (PSS-10; N = 1), the Screen for Child Anxiety Related Disorders (SCARED; N = 1), the Self-Rating Anxiety Scale (SAS; N = 1) and the Self-Rating Depression Scale (SDS; N = 1). Twelve studies used one or more sleep-related QOL measures, 13,17,23,26,29,[33][34][35][36]42,44,47 with the most popular being the Pittsburgh Sleep Quality Index (PSQI; N = 8).…”
Section: Resultsmentioning
confidence: 99%
“…For studies where it was clear what mode was used for data collection, two used paper surveys, 25,44 six collected responses online, 17,26,34,39,42,45 three collected responses via phone 36,39,42 and one used in-person interviews. 23,36 In general, studies found that being an inpatient with COVID-19 negatively affected QOL and, in particular, many studies found a negative impact on mental health 13,17,29,34,42,44 and/or sleep quality. 13,17,23,26,29,33,34,42,44 However, many studies did not formally include a comparator group of those without COVID-19, making it difficult to isolate the causal effect of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…In hospitalized COVID-19 patients, Akinci et al found that the depression rate among those with poor sleep quality was significantly higher than that in those with good sleep quality but not in those with anxiety ( Akıncı and Melek Başar 2021 ). Although they did not perform multiple linear regressions, Samushiya et al demonstrated that the PSQI score had positive correlations with measurements of anxiety and depression ( Samushiya et al, 2022 ), but they excluded patients with severe COVID-19 (defined as CT4, saturation <93%, a respiratory rate >30 per min, stable elevation of the body temperature at >39°, the presence of multiorgan failure). Not all the investigations found relations between sleep quality and anxiety or depression.…”
Section: Discussionmentioning
confidence: 99%
“…A second group of studies focused on sleep disturbances in COVID-19 patients. All of these studies concluded that COVID-19 patients had poorer sleep quality, both subjects who had been hospitalized ( Akıncı and Melek Başar 2021 ; Samushiya et al, 2022 ; Al-Ameri et al 2022 ; Tanriverdi et al, 2022 ) and those who had not ( Karimi et al 2022 ; Malik et al, 2022 ). Only a few studies differentiated the effects regarding the severity of COVID-19, such as that by Chhajer et al ( Chhajer and Shukla 2022 ), which showed a poorer quality of sleep in the severe COVID-19 group (intensive care unit (ICU) admission).…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality has also been described in hospitalized and nonhospitalized COVID-19 patients (Akıncı and Melek Başar, 2021;Al-Ameri et al, 2022;Karimi et al, 2022;Malik et al, 2022;Samushiya et al, 2022). The prevalence of sleep disturbances ranges from 57 to 74.8% (Alimoradi et al, 2021;Jahrami et al, 2021), which makes sleep disturbances one of the most prevalent symptoms in PCC patients.…”
Section: Introductionmentioning
confidence: 97%